Mariia Dmytrivna Kultaieva – a bright personification of philosophical and pedagogical creativity - Віль Бакіров (Філософія освіти)
Words of gratitude and deep respect for Mariia Dmitrivna Kultaieva from her colleague and friend Vil Savbanovych Bakirov.